Obstetric complications and cesarean delivery in Nepal - Karkee, Rajendra; Lee, Andy; Khanal, Vishnu; Pokharel, P.; Binns, Colin (Elsevier Ltd, 2014)
Objective: To determine the incidence of obstetric complications, the stillbirth rate, and the factors associated with cesarean delivery in central Nepal. Methods: A community-based prospective cohort study was undertaken in the Kaski district during 2011–2012. In total, 701 women who were at least 5 months pregnant were recruited and interviewed. Participants were followed-up and interviewed again within 45 days after delivery. Results: Of the 658 women who remained in the cohort after 43 were lost to follow-up, 12 (1.8%) had stillbirths. Cesareans accounted for 13.3% of the total deliveries. Age, urban residency, college-level education, and particularly presence of intrapartum symptoms significantly increased the likelihood of cesarean delivery. Prepartum, intrapartum, and postpartum symptoms were reported by 21.1%, 24.4%, and 10.2% of women, respectively. Common danger signs included prolonged labor, severe abdominal pain, swollen hand and body, and heavy bleeding. Conclusion: Obstetric complications and stillbirth rates were relatively high in central Nepal. Cesarean delivery appeared to meet obstetric need and was performed with medical indication, particularly after the onset of labor.